2014
DOI: 10.1159/000360995
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Therapeutic Selective Neck Dissection in Laryngeal Cancer

Abstract: Background: The aim of this study was to evaluate the effectiveness of selective neck dissection (SND) in patients with laryngeal cancer and clinically positive cervical nodes. Subjects and Methods: A retrospective review of the clinical records of 58 consecutive untreated patients affected by laryngeal carcinoma and submitted to surgical treatment was performed. Results: Twenty-six (44.8%) patients received monolateral neck dissection and 32 (55.2%) bilateral neck dissection. A total of 90 hemineck dissection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that a large proportion of patients with LSCC who are clinically diagnosed with cervical LNM before operation and undergo cervical lymph node dissection during their operation have a negative pathological diagnosis after operation, which resulted in excessive treatment. 5 On the contrary, some clinically negative neck nodes are pathologically positive, leading to delay treatment or even a second operation. 6 Furthermore, indications for neck dissection and salvage laryngectomy for patients with LSCC without regional lymph node involvement before operation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that a large proportion of patients with LSCC who are clinically diagnosed with cervical LNM before operation and undergo cervical lymph node dissection during their operation have a negative pathological diagnosis after operation, which resulted in excessive treatment. 5 On the contrary, some clinically negative neck nodes are pathologically positive, leading to delay treatment or even a second operation. 6 Furthermore, indications for neck dissection and salvage laryngectomy for patients with LSCC without regional lymph node involvement before operation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In 28 out of 29 (96%) NDs, the involved neck nodes were within the scope of SND, or there was no viable rest tumor. This less aggressive form of ND has been shown to carry minimal surgical morbidities but with comparable oncological outcomes [26]. Hanai et al[27] reported similar results in their study of N2–3 oropharyngeal and hypopharyngeal carcinoma patients: SND of levels II, III, and IV included 88% of positive neck nodes.…”
Section: Discussionmentioning
confidence: 89%
“…More than 95% of head-and-neck cancers are squamous cell carcinomas, suggesting that it is a homogeneous neoplasm when compared with other types of tumors [2]. Generally, using surgery combined with neck dissection, the gross tumor can be removed; however, the main difficulty for the surgeons lies in the residual of the microscopic tumor beyond the surgical margins, which causes recurrence after surgery [3]. So, for the most locally advanced head-and-neck cancers, radiotherapy either alone or postoperatively may achieve the optimal result because radiotherapy may kill the present or remaining cancer cells.…”
Section: Introductionmentioning
confidence: 99%